The Influence of Risk-Taking and Self-Confidence on MSME Performance - Reni Wijaya Wijaya; Darsih Darsih; Dorris Yadewani; Henny wati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines the influence of risk-taking and self-efficacy on the performance of MSMEs in Padang using a descriptive quantitative method and an ex post facto approach. Data was collected thru an online survey of 60 MSME actors using a standardized questionnaire. Data were analyzed using SPSS version 26 to test the relationship between variables. The results show that risk-taking and self- efficacy significantly influence MSME performance, assisting entrepreneurs in decision-making, strengthening competitiveness, and capitalizing on business opportunities. These findings indicate that psychological and sociocultural aspects play a significant role in the success of MSMEs. This research expands understanding of internal factors influencing the performance of small and medium-sized enterprises and provides recommendations for developing psychological-based training programs to promote MSME growth